ANALISIS KARAKTERISTIK KEWIRAUSAHAAN SEBAGAI FAKTOR PENENTU PERTUMBUHAN USAHA (Studi Kasus pada UMKM Martabak Setia Budi Semarang) - Muhammad Syawaludin Faiz; Ari Pradhanawati; Wahyu Hidayat (Universitas Diponegoro, 2015)
Characteristics of the entrepreneurial is a very important, entrepreneurial characteristics were action, abilities and otherspesific character that owned by someone who related to entrepreneurial activity. The purpose of this study were to know characteristics of the entrepreneurial business owners and how characteristics of the entrepreneurship role as a business growth factor in MSMEs Martabak Setia Budi Semarang. In this research using qualitative descriptive type.The technique of taking resources is purposive sampling; techniques of data collection is done by conducting interviews, observation, and documentation; data analysis techniques usingcredibility test data by triangulation, transferability test, and confirmability test.The results of this study showed that in the MSMEs Martabak Setia Budi, entrepreneurial characteristics of business owners is a determining factor in the business growth, which is seen from five aspects such as leadership, task orientation and results, confidence, risk-taking and future orientation that have been already good, Advice for MSMEs Martabak Setia Budi which must keep product quality, make innovation so the consumers are not bored and adding the number of employees at each branch.